Inflation, growth and policy coordination - Reside, Renato E., Jr (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1996)
The effect of monetary policy on output growth and inflation is examined in a monetary endogenous growth model with an explicit banking sector that intermediates capital. Monetary policy is coordinated with fiscal policy in the sense that all the seigniorage revenue gleaned through the inflation tax is spent to make efficient provision of public services. With the reserve requirement and money growth as instruments, policy coordination implies that one instrument may be solved endogenously when the other is predetermined. A higher reserve requirement being a binding constraint on capital creation generates adverse growth effects. On the other hand, by endogenously reducing the money growth rate, shiver reserve requirement lowers inflation. Interestingly, when public services are not productive, policies need not be coordinated. In this scenario, we derive a non-standard result wherein a rise in reserve requirements raises inflation. We conclude with the suggestion that differences in the degree of policy coordination account for cross-country differences in the persistence of inflation.